Psychogenic dystonia of the hand: A clinical case - A. I. Baidauletova; O. A. Shavlovskaya (Неврология, нейропсихиатрия, психосоматика, 2016)
The article describes a clinical case of psychogenic movement disorder appearing as fixed dystonia without pain. Over 5 years, a patient has had the right fingers being permanently clenched into a fist position at rest, which increased when fulfilling any motor task; carpal pain was absent. When he was 18 years old, the patient sustained a blast injury with concussion. A leather glove was used to reduce clenching and a makeshift device was applied to move the fingers apart. Motor function of the hand persisted; its atrophy was absent; muscle tone in the hand was sufficient; reflexes were symmetrical; sensitivity was not impaired. His gait, voice, speech were not changed. When writing, there was increased pencil grasp (not writer's cramp); his handwriting was smooth and legible. The patient uses the voluntary compensatory movements of the right hand (holding a thing with one hand in a supine position) and fingers (crossing the third finger over the fourth and conversely), which reduce the manifestations of movement disorder. He refused psychiatric examination and to take any medications.